Estimating Vitamin C Intake Requirements in Diabetes Mellitus: Analysis of NHANES 2017-2018 and EPIC-Norfolk Cohorts - Anitra C. Carr; Helen Lunt; Nicholas J. Wareham; Phyo K. Myint (MDPI AG, 2023)
Vitamin C is an essential enzyme cofactor and antioxidant with pleiotropic roles in human physiology. Circulating vitamin C concentrations are lower in people with diabetes mellitus, suggesting a higher dietary requirement for the vitamin. We interrogated the NHANES 2017-2018 and EPIC-Norfolk datasets to compare vitamin C requirements between those with and without diabetes mellitus using dose-concentration relationships fitted with sigmoidal (four-parameter logistic) curves. The NHANES cohort (n = 2828 non-supplementing adults) comprised 488 (17%) participants with diabetes (self-reported or HbA1c ≥ 6.5%). The participants with diabetes had a lower vitamin C status (median [IQR]) than those without (38 [17, 52] µmol/L vs. 44 [25, 61] µmol/L, p < 0.0001), despite comparable dietary intakes between the two groups (51 [26, 93] mg/d vs. 53 [24, 104] mg/d, p = 0.5). Dose-concentration relationships indicated that the group without diabetes reached adequate vitamin C concentrations (50 µmol/L) with an intake of 81 (72, 93) mg/d, whilst those with diabetes required an intake of 166 (126, NA) mg/d. In the EPIC-Norfolk cohort, comprising 20692 non-supplementing adults, 475 (2.3%) had self-reported diabetes at baseline. The EPIC cohort had a lower BMI than the NHANES cohort (26 [24, 28] kg/m2 vs. 29 [25, 34] kg/m2, p < 0.0001). Correspondingly, the EPIC participants without diabetes required a lower vitamin C intake of 64 (63, 65) mg/d while those with diabetes required 129 (104, NA) mg/d to reach adequate circulating vitamin C status. C-reactive protein concentrations were strongly correlated with body weight and BMI and provided a surrogate biomarker for vitamin C requirements. In conclusion, people with diabetes had 1.4 to 1.6 fold higher requirements for vitamin C than those without diabetes. This corresponds to additional daily vitamin C intake requirements of ~30-40 mg for people with diabetes, equating to a total daily intake of at least 125 mg/d.